Peran Ekoteologi Islam dalam Mendukung Green Economy dan Perilaku Ramah Lingkungan - Elen Wahyu Wijatmoko; Dian Tias Aorta (YASIN, 2026)
The increasing environmental problems resulting from community economic activities that pay insufficient attention to ecological sustainability indicate the importance of a religion-based value approach in developing environmentally friendly economic behavior. This study aims to analyze the role of Islamic ecotheological values in shaping environmentally friendly economic behavior among the community in Pringkuku Subdistrict. This study used a qualitative approach with a case study design. Data were obtained through interviews, observation, and documentation involving community members, religious leaders, and local economic actors. The results show that the community does not yet understand the concept of the green economy theoretically, but has implemented environmentally friendly economic behavior through habits of frugal living, maintaining environmental cleanliness, using natural resources wisely, and using organic fertilizers. Islamic ecotheological values, such as the concept of khalifah, the prohibition against causing damage, and the principle of simple living, play a role in shaping the community’s ecological awareness. However, the implementation of environmentally friendly behavior still faces obstacles in the form of low environmental literacy, limited waste management facilities, and the influence of modern consumerist culture. This study concludes that religious values make an important contribution to supporting the implementation of the green economy in rural communities. The implications of this study indicate that an ecological approach based on religious values can serve as an alternative strategy for building environmental awareness and supporting sustainable community development.